Essays on macroeconomic uncertainty - Smietanka, Pawel (2016)
Recent data shows that more than £440 billion in cash has been piling up in the accounts of UK companies. At the same time, the investment outlays and corporate payouts have reached a 60-year low. What makes firms hold such enormous cash stocks instead of spending them on investment or returning them to shareholders? To what extent has the rising degree of uncertainty about macroeconomic conditions affected companies’ decisions?